2021
DOI: 10.1186/s12875-020-01328-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the scope of practice on family physicians: a systematic review

Abstract: Background Family medicine is a branch of medicine that manages common and long-term illnesses in children and adults. Family physicians in particular play a major role and their scope of practice is expected to impact patient and population. However, little is known about its impact on physicians. We aimed to assess the effects of scope of practice on family physician outcomes. Methods We performed a systematic review that we reported using PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…There are some successful examples of rural-oriented medical schools, such as Jichi Medical University in Japan, James Cook University in Queensland, Australia, and Memorial University in St. John's, Canada [28][29][30]. Although these efforts contribute to the maintenance of rural healthcare to a certain degree, there is a need for additional incentives such as a scholarship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some successful examples of rural-oriented medical schools, such as Jichi Medical University in Japan, James Cook University in Queensland, Australia, and Memorial University in St. John's, Canada [28][29][30]. Although these efforts contribute to the maintenance of rural healthcare to a certain degree, there is a need for additional incentives such as a scholarship.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Japan is implementing various strategies for rural healthcare maintenance such as providing scholarships in exchange for postgraduate rural services [ 27 ]. There are some successful examples of rural-oriented medical schools, such as Jichi Medical University in Japan, James Cook University in Queensland, Australia, and Memorial University in St. John’s, Canada [ 28 - 30 ]. Although these efforts contribute to the maintenance of rural healthcare to a certain degree, there is a need for additional incentives such as a scholarship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that 9% of all family physicians practicing in hospitals stayed in practice because they oversaw inpatient hospice and palliative care. Some family physicians may have a passion for teaching, research, or management [29], which is not possible in a clinic setting. Some family physicians stay in hospitals for continuing education credits.…”
Section: Discussionmentioning
confidence: 99%
“…When appropriate, the SPOR Evidence Alliance research team collaborates with other SPOR entities to respond to a query. For example, the Ministère de la Santé et des Services sociaux (Québec Ministry of Health and Social Services) reached out to the SPOR Evidence Alliance in April 2018 seeking evidence on the scope of family physician practice to inform a position statement on the nature of family practice in Quebec (Zomahoun et al 2021). To respond to this query, the SPOR Evidence Alliance partnered with the knowledge synthesis platform of the Québec SUPPORT Unit, which is the provincial research service centre funded by the SPOR enterprise.…”
Section: How Does the Spor Evidence Alliance Build Researcher Capacity?mentioning
confidence: 99%